Islamic Performance Instrument (IPI): An alternative Servant Leadership (SL) tool for Sustainable Development Goals (SDGs) - Ogunsola, Kazeem Olanrewaju; Mhd. Sarif, Suhaimi; Fontaine, Rodrigue Ancelot Harvey (Fakultas Ekonomi, Universitas Islam Sultan Agung, 2020)
In the search for measures to keep the society sustained, a qualitative study was conducted to explore a Tawhidic Paradigm (TP) alternative for servant leaders, building upon Greenleaf servant leadership (SL) theory. The aim is to ground an Islamic Performance Instrument (IPI) favourable to sustainable development (SD). Adopting Charmaz's (2006) constructivist Grounded Theory Method (GTM), 5 Muslim managers were identified and interviewed through purposive sampling. The coding process produced an IPI-5es principles (expertise, ethereal, emotional, ethical and empowering) essentially required by servant leaders to transform SDGs around the globe. The Islamic constructs of ‘Aqidah (Creed), Khalifa (Vicegerent) and ‘Adl (Justice) were critical in grounding these principles. Theoretically, the research outcome contributes to body of knowledge on Tawhidic Paradigm (TP) and Islamic Servant Leadership (ISL). This paper projects leaders forming polices that synchronizes meeting SDGs with spiritual responsibilities. Practically, it offers leaders the ideal purpose of SL: servitude to the Creator – (Allah) and, also to humanity (fulfilling SDGs), as against the conventional SL theory which excludes the former. By implication, TP projects service to humanity (SDGs) as acts of worship (Ibadah). The paper was limited by fewer GTM research on Islamic SL principles for SDGs. Future study may conduct a time series analysis on servant leaders imbued with IPI-5es principles to determine SDGs success rate. The paper offers a pioneer model (IPI-5es principles) that extends conventional SL theory for SD.